Field research on the trinity energy storage and heating system of villa in cold area. (September 2022) - Wu, XuMing; Wu, ZhongMing; Luo, Ning; Wang, LiJin; Yang, RuiLan; Du, Shuai; Lian, ZhiYu
Abstract: Since the implementation of changing coal into clean energy heating in the Beijing–Tianjin–Hebei region, there has been a tremendous change in terms of air quality during the winter in the north. On the basis of field research for resort sample room setting up in the Yanqing district, Beijing, this paper mainly expounds the cold and heat sources and system solutions used by resort villas to meet the needs of hot water, heating, and cooling throughout the year, and introduces a new type of solar energy 'The heat pump direct floor radiant heating system' (called "Trinity"), which can combine air source heat pump-solar system and direct floor radiant heating to ensure the efficient and stable operation of the heating system while making full use of solar energy. Moreover, with the combination of modeling analysis on the annual load via DeST software, the result of actual measurement sees "Trinity" system as the optimal solution not only by means of comparing the heating scheme of the original single air source heat pump unit and the solar energy + air source heat pump unit's simulation comparison, it was concluded that the initial investment of scheme two was 16, 969 yuan and the initial investment of scheme two was 17, 352 yuan. The annual operating cost of the second option is 3577.8 yuan, and the annual operating cost of the second option is only about one-half of the annual operating cost of the second option. Based on the calculation of the investment recovery period, the cost savings of the second option after only 0.15 years is net income. Therefore, the "Trinity" scheme is selected as the best scheme.